Caracterização dos hábitos de sono, sonolência diurna e qualidade do sono em professores universitários das áreas biomédica e tecnológica - Borges, Galileu Rodrigues (2016)
The expression of sleep/wake cycle is the result of interactions among individual characteristics, sleep knowledge and habits, and social environment. In studies in teachers of primary and secondary school, it was observed poor sleep quality, excessive daytime sleepiness in half of the sample, besides sleep deprivation. Thus, an investigation in university professors is important. Besides teaching, they develop research activities and community outreach, and in some cases, administrative functions. The aim of this study was to characterize comparatively the habits and knowledge about sleep, sleep quality and daytime sleepiness in teachers of an institution of higher education of biomedical and technological areas. These aspects were evaluated through questionnaires: 1. Sleep and Health, 2. Pittsburg Sleep Quality Index, 3. Epworth Sleepiness Scale, and 4. chronotype evaluation of Horne and Ostberg (HO). Moreover, the pattern of sleep and wakefulness, and the working hours were recorded through 5. Sleep logs and 6. Daily activities protocol, which were filled for 10 days. The participants were 86 teachers, 44 (23 women) from the biomedical area and 47 (14 women) from the technological one. The work starting time (BM: 9:53h ± 1:30h; TC: 10:05h ± 2:30h) and the duration of work in the institution (BM: 7:30h ± 1:27h; TC: 7:30h ± 1:28h) did not differ between areas. However, the work finish time was later in technological area (BM: 18:10h ± 1:35h; TC: 18:48h ± 1:24h – ANOVA, p < 0.05). There was a trend to a higher total workload in the biomedical area (ANOVA, p = 0.06). Besides, the workload dedicated to teaching in postgraduate programs, as well as the number of post-graduate students were higher in this area (ANOVA, p <0.05). Teachers of biomedical area showed a higher percentage of correct answers about sleep knowledge, accompanied by better sleep hygiene habits (X2, p < 0.05). The bedtimes (BM: 23:53h ± 15min; TC: 23:31h ± 22min), the wake up times (BM: 6:46h ± 40min; TC: 7:40h ± 30min) and the time in bed (BM: 6:58h ± 60 min; TC: 7:12h ± 55min) did not differ between areas (ANOVA, p > 0.05). Despite that, biomedical teachers showed a tendency towards morningness in relation to teachers of technological area (X2, p < 0.05). In relation to quality of sleep and daytime sleepiness, there was a higher percentage of good quality accompanied by a lower percentage of excessive daytime sleepiness in the biomedical field. These differences in the parameters of sleep may be related to better sleep hygiene habits and knowledge about sleep in teachers of biomedical area. Thus, it is suggested that the professional area influence the knowledge about sleep with impacts to sleep habits, producing effects on quality and daytime sleepiness of university professors. This background reinforces the need of development of sleep educational programs with university professors in an attempt to promote better sleep habits and consequently better quality of life, health and academic productivity in these professionals.